Can Policy Change Culture? Government Pension Plans and Traditional Kinship Practices - Bau, Natalie (American Economic Review, 2021)
Policies may change the incentives that allow cultural practices to persist. To test this, I study matrilocality and patrilocality, kinship traditions that determine daughters’ and sons’ post-marriage residences, and thus, which gender lives with and supports parents in their old age. Two separate policy experiments in Ghana and Indonesia show that pension policies reduce the practice of these traditions. I also show that these traditions incentivize parents to invest in the education of children who traditionally coreside with them. Consequently, when pension plans change cultural practices, they also reduce educational investment. This finding further demonstrates that policy can change culture. (JEL G51, I20, J15, J16, J32, Z13)